Lower GDNF Serum Level Is a Possible Risk Factor for Constipation in Patients With Parkinson Disease: A Case–Control Study - Chen, Gang; Du, Yinzhen; Li, Xue; Kambey, Piniel Alphayo; Wang, Li; Xia, Ying; Tang, Chuanxi; Shi, Mingyu; Zai-li, Li; Zai-e, Xin; Xiao-ling, Qin; Dian-shuai, Gao (Frontiers in Neurology, 2022)
Abstract Background: Constipation is a significant symptom of Parkinson's disease. Glial-derived neurotrophic factor (GDNF) is important for the morphogenesis of the enteric nervous system (ENS) and plays a critical role in the preservation of mucosal integrity under enteric glia surveillance. The aim of this study was to evaluate the serum levels of GDNF in Parkinson's disease patients with and without constipation. Methods: This study included 128 Parkinson's disease patients. The patients were classified into three groups: those with PD but no constipation (nCons-PD) (n = 49), those with prodromal stage constipation (Cons-Pro-PD) (n = 48), and those with clinical stage constipation (Cons-Clinic-PD) (n = 31). The association between serum GDNF concentration and constipation was explored using logical regression. Results: The nCons-PD group's mean GDNF levels were 528.44 pg/ml, which was higher than the Cons-Pro-PD group's 360.72 pg/ml and the Cons-Clinic-PD group's 331.36 pg/ml . The results of binary logistic regression indicated that GDNF was a protective factor in the prevention of constipation. Cons-Clinic-PD group had a higher score of MDS-UPDRS-Ⅱ, MDS-UPDRS-Ⅲ, MDS-UPDRS-Ⅳ, and a higher H-Y staging as compared to nCons-PD group. Relative to the nCons-PD group, Cons-Clinic-PD had higher NMSS scores, lower MoCA and PDSS scores, and were more likely to have RBD. Conclusions: GDNF serum levels are lower in Parkinson's disease patients who are constipated. A low GDNF level is a potential risk factor for constipation in Parkinson's disease patients.